2023
DOI: 10.1093/pubmed/fdad001
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on suicide because of social isolation/and loneliness: does COVID-19 make a difference?

Abstract: Background Suicide is a significant cause of death worldwide. Various purposes can explain why people choose to attempt or commit suicide such as mental-health disorders, income-related-factors, quality of life or issues related to social context. This study aims to identify an updated association between ‘isolation’ and suicides. Methods In this regard, we had made a systematic review of the most recent papers, published fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…These findings align with the results of systematic reviews (Dalekou et al 2023;Zhao et al 2023;Bozzola et al 2023) and can be explained by the heavy impact of strict confinement measures put in place by public health authorities at the onset of the pandemic, which led to school closures, the interruption of extracurricular sports activities, and the need to organize a healthy routine at home. For many parents of children and adolescents, this was a major challenge as they had to balance childcare, domestic and work activities (Fadda et al 2023;Blázquez-Fernández et al 2023). The consequences were that children and adolescents were oftentimes left to themselves but did not yet have the means to effectively structure their day and care for themselves.…”
Section: Discussionmentioning
confidence: 99%
“…These findings align with the results of systematic reviews (Dalekou et al 2023;Zhao et al 2023;Bozzola et al 2023) and can be explained by the heavy impact of strict confinement measures put in place by public health authorities at the onset of the pandemic, which led to school closures, the interruption of extracurricular sports activities, and the need to organize a healthy routine at home. For many parents of children and adolescents, this was a major challenge as they had to balance childcare, domestic and work activities (Fadda et al 2023;Blázquez-Fernández et al 2023). The consequences were that children and adolescents were oftentimes left to themselves but did not yet have the means to effectively structure their day and care for themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Young individuals are especially vulnerable to loneliness as they are in a state of social, psychosocial and cognitive transition from childhood to adulthood [37]. The increased loneliness prevalence causes public health concerns, as it is associated with risk factors such as suicidal behaviour [38,39], social anxiety and depression [40] as well as future adult psychological illness and poor health outcomes [41].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the COVID-19 pandemic has badly impacted the social life of students as it has resulted in less interaction with friends, classmates and tutors. This isolated environment has limited their activity and intensified feelings of laziness and worthlessness leading to negative repercussions on their psychological well-being (Blázquez-Fernández, Lanza-León, & Cantarero-Prieto, 2023; Fawaz & Samaha, 2021). A multicenter study conducted during the COVID-19 crisis on participants aged 15 to 24 years showed that the overall prevalence of stress, anxiety and depression was 38.1%, 40.5% and 57%, respectively (Al Omari et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%